Pengaruh Home Visit Terhadap Penurunan Episode Penyakit Infeksi dan Peningkatan Angka Kecukupan Gizi pada Balita Malnutrisi Akut Berat - Titih Huriah (Alma Ata University Press, 2017)
Malnutrition is one of the principal causes of child mortality in developing countries including Indonesia. Severe Acute Malnutrition (SAM) is the most serious form of malnutrition affecting children under-five and is associated with many infectious diseases and nutrition intake. In the last few decades, there has been a paradigm shift in the management of acute malnutrition from a facility-based to community-centered approach. The purpose of this study was to evaluate effect of home care intervention in decreasing infectious diseases episode and increasing nutrition intake of severe acute malnutrition children aged 6-60 months. Quasi-experimental with pretest-posttest control group design was carried out for this study. The study was done in two district involving 32 health centers of Yogyakarta province. 56 children with SAM were selected using purposive sampling. The study was performed in three phases, intensive, strengthening and independent phase applying nursing care approach. Data analysis was done by SPSS software. Mean episodes of infectious diseases in the baseline at home care group was 2,64 days and after the intervention the mean was 0,21 days. Nutritional adequacy rate in the baseline only reached 83,65% and after intervention reached 106,23%. During the three months intervention of home care, there were significant decreases in infectious diseases episode and increases nutrition intake with p value 0,0003 and 0,003 respectively